Detecting cross‐equatorial wind change as a fingerprint of climate response to anthropogenic aerosol forcing. Issue 7 (6th April 2016) - Wang, Hai; Xie, Shang‐Ping; Tokinaga, Hiroki; Liu, Qinyu; Kosaka, Yu
Abstract: Anthropogenic aerosols are a major driver of the twetieth century climate change. In climate models, the aerosol forcing, larger in the Northern than Southern Hemispheres, induces an interhemispheric Hadley circulation. In support of the model result, we detected a robust change in the zonal mean cross‐equatorial wind over the past 60 years from ship observations and reanalyses, accompanied by physically consistent changes in atmospheric pressure and marine cloud cover. Single‐forcing experiments indicate that the observed change in cross‐equatorial wind is a fingerprint of aerosol forcing. This zonal mean mode follows the evolution of global aerosol forcing that is distinct from regional changes in the Atlantic sector. Atmospheric simulations successfully reproduce this interhemispheric mode, indicating the importance of sea surface temperature mediation in response to anthropogenic aerosol forcing. As societies awaken to reduce aerosol emissions, a phase reversal of this interhemispheric mode is expected in the 21st century. Key Points: A model‐observation synergy is developed to identify the anthropogenic aerosol‐induced climate change Cross‐equatorial antisymmetric pattern is a fingerprint of aerosol forcing Zonal mean cross‐equatorial energy transport theory is validated observationally